Answer:
the first selection is so shaded
Step-by-step explanation:
Each strip is divided into 10 parts. 1/5 will be represented by 2 of those parts, so 2/5 will be represented by 4 of the 10 parts. The 3/10 used on the other gift will be represented by 3 additional parts. So, a total of 7 of the 10 parts of the strip need to be colored to represent the ribbon used.
<h2>
Answer with explanation:</h2>
We are asked to prove by the method of mathematical induction that:
![2^n\leq 2^{n+1}-2^{n-1}-1](https://tex.z-dn.net/?f=2%5En%5Cleq%202%5E%7Bn%2B1%7D-2%5E%7Bn-1%7D-1)
where n is a positive integer.
then we have:
![2^1\leq 2^{1+1}-2^{1-1}-1\\\\i.e.\\\\2\leq 2^2-2^{0}-1\\\\i.e.\\2\leq 4-1-1\\\\i.e.\\\\2\leq 4-2\\\\i.e.\\\\2\leq 2](https://tex.z-dn.net/?f=2%5E1%5Cleq%202%5E%7B1%2B1%7D-2%5E%7B1-1%7D-1%5C%5C%5C%5Ci.e.%5C%5C%5C%5C2%5Cleq%202%5E2-2%5E%7B0%7D-1%5C%5C%5C%5Ci.e.%5C%5C2%5Cleq%204-1-1%5C%5C%5C%5Ci.e.%5C%5C%5C%5C2%5Cleq%204-2%5C%5C%5C%5Ci.e.%5C%5C%5C%5C2%5Cleq%202)
Hence, the result is true for n=1.
- Let us assume that the result is true for n=k
i.e.
![2^k\leq 2^{k+1}-2^{k-1}-1](https://tex.z-dn.net/?f=2%5Ek%5Cleq%202%5E%7Bk%2B1%7D-2%5E%7Bk-1%7D-1)
- Now, we have to prove the result for n=k+1
i.e.
<u>To prove:</u> ![2^{k+1}\leq 2^{(k+1)+1}-2^{(k+1)-1}-1](https://tex.z-dn.net/?f=2%5E%7Bk%2B1%7D%5Cleq%202%5E%7B%28k%2B1%29%2B1%7D-2%5E%7B%28k%2B1%29-1%7D-1)
Let us take n=k+1
Hence, we have:
![2^{k+1}=2^k\cdot 2\\\\i.e.\\\\2^{k+1}\leq 2\cdot (2^{k+1}-2^{k-1}-1)](https://tex.z-dn.net/?f=2%5E%7Bk%2B1%7D%3D2%5Ek%5Ccdot%202%5C%5C%5C%5Ci.e.%5C%5C%5C%5C2%5E%7Bk%2B1%7D%5Cleq%202%5Ccdot%20%282%5E%7Bk%2B1%7D-2%5E%7Bk-1%7D-1%29)
( Since, the result was true for n=k )
Hence, we have:
![2^{k+1}\leq 2^{k+1}\cdot 2-2^{k-1}\cdot 2-2\cdot 1\\\\i.e.\\\\2^{k+1}\leq 2^{(k+1)+1}-2^{k-1+1}-2\\\\i.e.\\\\2^{k+1}\leq 2^{(k+1)+1}-2^{(k+1)-1}-2](https://tex.z-dn.net/?f=2%5E%7Bk%2B1%7D%5Cleq%202%5E%7Bk%2B1%7D%5Ccdot%202-2%5E%7Bk-1%7D%5Ccdot%202-2%5Ccdot%201%5C%5C%5C%5Ci.e.%5C%5C%5C%5C2%5E%7Bk%2B1%7D%5Cleq%202%5E%7B%28k%2B1%29%2B1%7D-2%5E%7Bk-1%2B1%7D-2%5C%5C%5C%5Ci.e.%5C%5C%5C%5C2%5E%7Bk%2B1%7D%5Cleq%202%5E%7B%28k%2B1%29%2B1%7D-2%5E%7B%28k%2B1%29-1%7D-2)
Also, we know that:
![-2](https://tex.z-dn.net/?f=-2%3C-1%5C%5C%5C%5Ci.e.%5C%5C%5C%5C2%5E%7B%28k%2B1%29%2B1%7D-2%5E%7B%28k%2B1%29-1%7D-2%3C2%5E%7B%28k%2B1%29%2B1%7D-2%5E%7B%28k%2B1%29-1%7D-1)
(
Since, for n=k+1 being a positive integer we have:
)
Hence, we have finally,
![2^{k+1}\leq 2^{(k+1)+1}-2^{(k+1)-1}-1](https://tex.z-dn.net/?f=2%5E%7Bk%2B1%7D%5Cleq%202%5E%7B%28k%2B1%29%2B1%7D-2%5E%7B%28k%2B1%29-1%7D-1)
Hence, the result holds true for n=k+1
Hence, we may infer that the result is true for all n belonging to positive integer.
i.e.
where n is a positive integer.
Answer: 5,000 square feet
Step-by-step explanation:
50 feet multiplying by 100 feet equal to 5,000 sq ft.